2013
DOI: 10.4028/www.scientific.net/msf.762.590
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Numerical Simulations of the Microstructure Evolution in AA6082 during Friction Stir Processing by Means of Hot Torsion and FEM

Abstract: A reproduction of the conditions occurring during friction stir processing, where a fine grained structure according to the process parameters rpm, transverse speed and pressure develops is the main focus in the present work. To physically simulate such a friction stir process, hot torsion tests at constant temperatures were carried out in a Gleeble ® 3800 machine at different strains and strain rates. The specimens were immediately water quenched after hot deformation to avoid any static recrystallization. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…It has been revealed that in the friction stir processing (FSP) of aluminium alloys, the microstructure in the NG is deformed to a very large extent and grain rotation at high cyclic strains takes place [41]. The present experimental results reveal that the activity of grain boundary cracking as such suggests that some more grain rotation did occur.…”
Section: Cyclic Behaviour and Microstructural Evolutionmentioning
confidence: 75%
“…It has been revealed that in the friction stir processing (FSP) of aluminium alloys, the microstructure in the NG is deformed to a very large extent and grain rotation at high cyclic strains takes place [41]. The present experimental results reveal that the activity of grain boundary cracking as such suggests that some more grain rotation did occur.…”
Section: Cyclic Behaviour and Microstructural Evolutionmentioning
confidence: 75%